Evaluation of antireflux surgery effectiveness in patients with hiatal hernia - A. V. Klymenko; B. S. Kravchenko; V. M. Klymenko; L. N. Serhieieva; S. M. Kravchenko; V. S. Tkachov (Zaporozhye State Medical University, 2023)
The generally accepted gold standard in the surgical treatment of hiatal hernias is laparoscopic fundoplication with cruroplasty. At the same time, the problem of choosing the best method of fundoplication to improve the results of surgical intervention remains disputable. Aim. Determination of the effectiveness of antireflux interventions and the frequency of postoperative dysphagia in patients with esophageal hernia. Materials and methods. The results of 38 patients in the early and late postoperative period, operated with the use of Nissen and Toupet fundoplication, with an integrated exhaustive examination of the manifestations of dysphagia syndrome were analyzed. 17 (44.7 %) patients (first group) underwent laparoscopic posterior crurorraphy with Nissen fundoplication in the Short-Floppy-Nissen modification, and 21 (55.3 %) patients (second group) underwent posterior crurorraphy with Toupet fundoplication. Results. In the postoperative period, the intensity of pain on the rating scale was minimal in 70.6 % and 71.4 %; moderate in 23.5 % and 14.3 %; strong in 5.9 % and 14.3 % of the patients in the first and second groups, respectively. The first degree of dysphagia (the ability to ingest liquid food and fluids) was observed in 5 of 17 (29.4%) patients of the first group, with subsequent regression in 4 of 5 patients within 5 days; in the second group there was no dysphagia. When comparing the results of all scales of integrated analysis of the quality of life of the patients of both groups, no significant difference was found between them. Conclusions. The obtained data demonstrate the compatibility of both methods, in the absence of differences in quality of life and patient's satisfaction in the late postoperative period. Differences in the frequency of dysphagia syndrome after surgery indicate the need for a more differentiated approach to the choice of fundoplication technique.